Engineering a Plant-Derived Astaxanthin Synthetic Pathway Into Nicotiana benthamiana - Allen, Quinton M.; Febres, Vicente J.; Rathinasabapathi, Bala; Chaparro, José X. (Frontiers in Plant Science, 2022)
Carotenoids have been shown to be essential for human nutrition. Consumption of carotenoid-rich fruits and vegetables can reduce the risk of many diseases. The ketocarotenoid astaxanthin has become a commercially valuable compound due to its powerful antioxidant properties compared to other carotenoids. It is naturally produced in certain algae, bacteria, and the flowers of some species of the genus Adonis, although it is produced in such small quantities in these organisms that it is costly to extract. Chemical synthesis of this compound has also shown limited success with a high proportion of esterified forms of astaxanthin being produced, which decreases antioxidant properties by the conversion of hydroxyl groups to esters. Previously, transgenic astaxanthin-producing plants have been created using a β-carotene ketolase enzyme of either bacterial or algal origin. However, a novel astaxanthin pathway exists in the flowering plants of the genus Adonis which has not been utilized in the same manner. The pathway involves two unique enzymes, β-ring-4-dehydrogenase and 4-hydroxy-β-ring-4-dehydrogenase, which add the necessary hydroxyl and ketone groups to the rings of β-carotene. In the present study, Nicotiana benthamiana plants were transformed with chimeric constructs coding for these two enzymes. The regenerated, transgenic plants accumulate astaxanthin and their growth (height and weight) was unaffected, when compared to non-transformed N. benthamiana and to plants transformed with the bacterial β-carotene ketolase. The accumulation of astaxanthin also improved seedling survivability under harsh UV light, mitigated reactive oxygen accumulation, and provided a phenotype (color) that allowed the efficient identification and recovery of transgenic plants with and without selection.